Switzerland’s Sanctions Policy towards Russia during the 2022 Ukraine Conflict: A Constructivist Perspective - Hamel, Michael Christopher; Indrawati, Indrawati; Abubakar, Ibrahim (Indonesian Scientific Publication, 2025)
This research examines Switzerland's sanctions policy towards Russia during the 2022 Ukraine conflict, utilizing Martha Finnemore's constructivist approach. Switzerland is widely known for its long-standing commitment to human rights, as well as its traditional inclination toward neutrality in international affairs. This study seeks to understand why, despite its cautious stance in most global conflicts, Switzerland chose to adopt the European Union's sanctions in response to serious violations of international humanitarian law committed during the Russian invasion of Ukraine. Employing a qualitative descriptive method through literature review and policy analysis, the research applies Finnemore's concept of ideas and norms to explore how deeply rooted human rights values shape Swiss foreign policy behavior. The findings reveal that the sanctions imposed by Switzerland are not merely political gestures, but rather a reflection of human rights norms that have been internalized through its constitution, legal system, and long-standing role in international humanitarian institutions. The study concludes that Switzerland's decision represents a consistent normative commitment to defend universal human rights and uphold the principles of international law.